Imaginative Image-Based Learning Media Innovation to Improve Creativity and Psychomotor Abilities in Elementary Schools - Nur Fazria Masfufah; Nurdyansyah Nurdyansyah (Yayasan Keluarga Guru Mandiri, 2023)
In this elementary school, the creativity and psychomotor abilities of students in drawing are not good enough so researchers want to make imaginative drawing media to increase the creativity and psychomotor abilities of students and to determine the feasibility, practicality, and effectiveness of using media in strengthening creativity and psychomotor abilities. This research used the research and development (RD) method to make certain products and test how well these products are used. The model used was the design of the Borg and Gall development model. Researchers collected data using questionnaires, document checklists, and documentation. The research subjects were 4th-grade students at an elementary school in Sidoarjo, East Java, totaling 30 students. Based on the validation test from media experts and learning design, an average value of 90% was obtained, which means it is very feasible to use. The product development practicality test obtained an average score of 3.89 (98.25%) included in the very attractive category. It can be concluded that this imaginative drawing e-module is practical, interesting, and effective as a learning medium. The results of the t-test showed that there was a significant increase in the average learning outcomes of students' creativity and psychomotor abilities after receiving a different treatment, namely using the Imaginative Drawing e-Module. It can be concluded that this imaginative image media is practical, interesting, and effective as a learning medium.